Mengaplikasikan Model Pembelajaran Interaktif Berbasisctl (Contextual Teaching and Learning) Terhadap Hasil belajar Siswa pada Mata Pelajaran IPA - Rizka Ghina Fauziyah; Ibnu Muthi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to evaluate the effectiveness of the interactive learning model based on Contextual Teaching and Learning (CTL) on student learning outcomes in science subjects for second-grade elementary school students, particularly on the topic of recognizing plants as living organisms. The research method used is a Systematic Literature Review (SLR). Literature search was conducted through academic databases such as Google Scholar,, and PubMed using keywords like “Contextual Teaching and Learning,” “CTL,” “science learning outcomes,” “elementary education,” and “recognizing plants.” From the several potential articles identified, a selection of articles met the inclusion criteria and were analyzed in-depth. The analysis results indicate that the application of the CTL model consistently improves student learning outcomes, as evidenced by enhanced conceptual understanding, learning motivation, and active student participation in the classroom. The analyzed studies reported a significant increase in the average learning outcomes of students following the implementation of CTL. Additionally, this learning model makes learning more meaningful and relevant to the students’ daily lives. In conclusion, the CTL learning model is effective in enhancing student learning outcomes in science subjects for second-grade elementary school students, implying that schools and educators should consider the broader adoption of CTL and provide adequate support and training for teachers.